Improving English Writing Skills Using Text-Based Learning Methods and Group Work - Nurmayana, Nurmayana; Hariati, Puji; Siahaan, Desta Gloria (Universitas Pahlawan Tuanku Tambusai, 2024)
Students are required to master several skills. One of the skills that students must master in English subjects is text writing skills. It's just that the fact is that not all students are able to write well because of the lack of training provided by lecturers. Therefore, this research aims to analyze the use of text-based learning methods and group work on writing skills in UPMI students. This research uses a classroom action research method which is carried out in two cycles. The subjects of this research were Management Students at the Indonesian Community Development University (UPMI), totaling 35 students. Data collection in research was carried out using test methods and questionnaire methods. The research results show that the use of text-based learning methods and group work can improve students' writing skills. The average value of descriptive text writing skills in cycle I was 70.43 with a success of 34.28%. There was an increase in cycle II with an average student score of 78.86 with success of 77.14%. Student responses in cycle I were 40.11 in the positive category, while in cycle II it increased to 43.74 in cycle II in the positive category. So, the results of this research indicate an increase in students' descriptive text writing skills after learning using text-based learning methods and group work.